The most efficient contribution of shear walls in dual structural systems in medium height buildings [electronic resource] - Meisam Ansari, 1982- (2011)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2011